2015
DOI: 10.1016/j.lwt.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of Tuscan Artemisia annua essential oil and its major components against some foodborne pathogens

Abstract: Recently, the attention of researchers regarding Artemisia annua has been focused on the antimicrobial activity of the essential oil. This oil, rich in mono- and sesquiterpenes, has a strong activity against some Gram-negative and Gram-positive bacteria.\ud The aim of our study is to further contribute to the knowledge of the antibacterial activity of an Artemisia annua essential oil collected in Tuscany and its three most represented compounds (artemisia ketone, 1,8-cineole and camphor).\ud The essential oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 16 publications
2
48
0
1
Order By: Relevance
“…The initial temperature of the column was 60°C for 2 min; then, it was raised to 240°C at 8°C min À1 and held there for 5 min. One microlitre samples (0.8 mg mL À1 ) were injected in the split mode (1:50) (Diao et al, 2014;Donato et al, 2015).…”
Section: Chemical Compositions Of Aaomentioning
confidence: 99%
See 1 more Smart Citation
“…The initial temperature of the column was 60°C for 2 min; then, it was raised to 240°C at 8°C min À1 and held there for 5 min. One microlitre samples (0.8 mg mL À1 ) were injected in the split mode (1:50) (Diao et al, 2014;Donato et al, 2015).…”
Section: Chemical Compositions Of Aaomentioning
confidence: 99%
“…Essential oils, odorous and volatile products of plant secondary metabolism, have been widely applied in folk medicine as antimicrobial agents. Artemisia annua, belonging to the Asteraceae family, is native to China and now naturalised in many other countries (Donato et al, 2015). The A. annua has been used in therapy for recent decades because it is the unique source of artemisinin (Isacchi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Artemisia annua L. is a well-known species since it contains the powerful antimalarial drug artemisinin, discovered by the Chinese researcher Youyou Tu in 1972 who was awarded the Nobel Prize for Medicine in 2015 [9]. The plant produces a characteristic essential oil (EO) evaluated in many studies for its antimicrobial activity against bacteria and fungi [10][11][12][13]. The profile of A. annua EO constituents is rather variable, sometimes reflecting a non-uniformity of bioactivity results.…”
mentioning
confidence: 99%
“…It is important to consider that the quality and yield of essential oils from Artemisia species is influenced by different factors such as harvesting season, pH of soils, geographic location, choice of plant part, and extraction method [8,10]. Most of the studies related to the activities of A. annua EO have been performed with direct contact of the essential oil with the microorganisms, using different types of assays, namely diffusion or dilution methods [10,11]. Recently, some attempts have been made to evaluate the antimicrobial activity of the EO vapour phase only [12,14].…”
mentioning
confidence: 99%
“…In their work, changes in the cellular structure of both microorganisms after contact with nanoemulsions containing different EOs can be observed in contrast with control cells. Results also showed that CIN exhibited antimicrobial activity against Salmonella Enteritidis and Salmonella Typhi (Donato et al, 2015 ). Due to the lipophilic nature of CIN, it is believed that CIN displayed antibacterial activity against Gram-negative pathogenic bacteria by inducing cell membrane disruption (Ojeda-Sana et al, 2013 ).…”
Section: Discussionmentioning
confidence: 98%